Can this be written -(125a^3-225a^2+135a-27)=-(5a-3)^3? Let's see:

(5a-3)^3=125a^3-(3(25a^2)*3+3(5a)*3^2-3^3)=

125a^3-225a^2+135a-27 (using the expansion of (x-y)^3=x^3-3x^2y+3y^2x-y^3, and putting x=5a and y=3).

Yes! Good guess because 125=5^3 and 27=3^3 so it's worth a shot at assuming initially that we have a perfect cube.

So the answer is -(5a-3)^3 or (3-5a)^3 (these are equivalent because -(x^3)=(-x)^3.

- All categories
- Pre-Algebra Answers 12,254
- Algebra 1 Answers 25,164
- Algebra 2 Answers 10,398
- Geometry Answers 5,143
- Trigonometry Answers 2,632
- Calculus Answers 5,925
- Statistics Answers 3,008
- Word Problem Answers 9,973
- Other Math Topics 6,512

81,009 questions

85,050 answers

2,130 comments

68,477 users